Teachers’ Professionalism in Enhancing Students’ Collaborative Skills and Information Technology: A Case Study at Senior High School - Rahmat Haluti; Hamdan Juhanis; Herson Anwar; Samsuddin Samsuddin (STAI Hubbulwathan Duri, 2025)
Teacher professionalism is essential in fostering students' collaborative skills and integrating information technology in learning. At SMA Negeri 1 Kabila, teachers face challenges in designing effective teaching modules and utilizing digital tools for hybrid learning. This study explores how teachers manage these challenges and enhance their professional competence. This qualitative research employs a phenomenological approach, with data collected through observations, interviews, and documentation. The study examines teachers' strategies in implementing collaborative learning and digital technology integration, particularly in Project-Based Learning (P5). Findings indicate that teacher professionalism is evident in collaborative teaching approaches and the use of digital platforms. Teachers work with colleagues to improve instructional methods and develop students’ character. Despite this, they encounter difficulties in designing hybrid learning modules and effectively using digital tools. To address these issues, teachers engage in guided and independent training, receive mentoring, and utilize tools like Flip PDF Professional for content development and data management. While teachers make efforts to enhance their competencies, ongoing challenges in hybrid learning persist. Training programs and digital tool adoption help bridge these gaps, improving both teaching effectiveness and student learning outcomes. Future research should explore the long-term impact of these strategies on student performance. Teacher professionalism plays a crucial role in adapting to modern educational demands. Continuous professional development and digital literacy training are essential for optimizing collaborative learning and technology integration in hybrid education.